Респираторная система клеща Varroa jacobsoni (Parasitiformes, Varroidae) - Акимов, И.А.; Ястребцов, А.В. (Вестник зоологии, 1984)
Respiratory System of the Mite Varroa jacobsoni (Parasitiformes, Varroidea). Akimov I. A, Yastrebtsov A. V.— Vestn. zool., 1984, No. 3. Respiratory system in Varroa

jacobsoni consists of 4 pairs of anterior and 4 pairs of superior tracheal stems, a pair of
stigmal orifices, situated laterally between III and IV pairs of coxae, and a pair of

peritremes, situated transversally. Preatrial and atrial chambers, giving the rise to
tracheal stems and peritremal tubes, are connected with stigmal orifices. Peritremes with

their ability to fold downward and stigmae have no own muscles. A complex peritremal
system is probably responsible for water balance at a mite transpiration. The active

breathing movements (2 to 5 times per min.) are due to opistosomal dors-ventral muscles
and external muscles of the walking legs. Under mite movement, tracheal ventilation is
continuous.